Night monkey, day monkey - Donaldson, Julia; Richards, Lucy (London : Egmont, 2008)
Trying to play together allows Day Monkey and Night Monkey to each see how the other views the world.
Compact disc.
1.6
K-3
Keywords: Friendship -- Juvenile fiction; Monkeys -- Juvenile fiction; Toleration -- Juvenile fiction; Friendship -- Fiction; Monkeys -- Fiction; Stories in rhyme; Toleration -- Fiction; Compact discs; Friendship -- Fiction; Monkeys -- Fiction; Stories in rhyme; Toleration -- Fiction; Compact discs